2019
DOI: 10.2147/ott.s195364
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNA-940 restricts the expression of metastasis-associated gene MACC1 and enhances the antitumor effect of Anlotinib on colorectal cancer</p>

Abstract: Background: Metastasis-associated with colon cancer-1 (MACC1) is an important regulator that promotes colorectal cancer (CRC) cells’ proliferation and distant metastasis. Therefore, MACC1 is considered as a promising therapeutic target of CRC. This work aimed to identify the microRNA (miR) targeted to MACC1, and to study the potential of using the particular miR in enhancing the antitumor effect of chemotherapy. Materials and methods: miR prediction was performed in the miR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 71 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…MicroRNAs (miRs) have a dual role in promoting drug sensitivity and inducing drug resistance in cancer treatment (28,29). A study by Wang et al (30) suggested that silencing the expression of the gene metastasis-associated in colon cancer-1 via miR-940 increased the antitumor effect of anlotinib on the proliferation and invasive growth of CRC cells. Ma et al (31) reported that miR-6077 inhibited the expression of glucose transporter 1 and enhanced the anti-tumor effect of anlotinib on patient-derived lung adenocarcinoma cells.…”
Section: Preclinical Studies On Anlotinibmentioning
confidence: 99%
“…MicroRNAs (miRs) have a dual role in promoting drug sensitivity and inducing drug resistance in cancer treatment (28,29). A study by Wang et al (30) suggested that silencing the expression of the gene metastasis-associated in colon cancer-1 via miR-940 increased the antitumor effect of anlotinib on the proliferation and invasive growth of CRC cells. Ma et al (31) reported that miR-6077 inhibited the expression of glucose transporter 1 and enhanced the anti-tumor effect of anlotinib on patient-derived lung adenocarcinoma cells.…”
Section: Preclinical Studies On Anlotinibmentioning
confidence: 99%
“…In patients with advanced medullary thyroid carcinoma and metastatic renal cell carcinoma, anlotinib also shows promising efficacy [8][9][10][11] . In human colorectal cancer, the antitumor effect of anlotinib can be enhanced by MiR-940 targeting MACC1's mRNA 12 . Similar to that of other receptor tyrosine kinase inhibitors, the combined treatment of anlotinib with chemotherapy does not appear to be more beneficial than anlotinib alone 13 .…”
Section: Introductionmentioning
confidence: 99%
“…31 It has also been reported that MACC1 is strongly associated with MET signaling in liver metastases of resected CRC and is involved in EMT in colorectal cancer. 32,33 However, our analysis showed that it was downregulated in liver cancer. Until now, no studies have been conducted to try to understand the differential expression of MACC1 between primary and metastatic liver tumors.…”
Section: Expression Of Genes Associated With the Warburg Effectmentioning
confidence: 67%